Eksplorasi Penggunaan Buku Digital dan Buku Fisik dalam Meningkatkan Minat Belajar Siswa Kelas XI di Sekolah Menengah Atas Negeri 1 Kisaran - Tampubolon, Cindy Febi Paola; Nasution, Wan Nurul Atikah; Kurniati, Sri (Jurnal Bahastra, 2025)
Reading is an essential activity in the learning process, as it plays a crucial role in expanding students' knowledge. Through reading, students gain access to various pieces of information that contribute to their moral and personal development. In the current digital era, technological advancements have significantly influenced education, including the increasing use of digital books or e-books. However, many students still prefer reading physical books over digital ones. The publishing industry and the profession of book writing continue to grow, with books being produced both in printed and digital formats. Each format has its own advantages and disadvantages. The study explores the impact of digital and physical books on reading habits and learning interest. The findings suggest that regardless of the format, maintaining a consistent reading habit is crucial for intellectual growth. Those who engage in frequent reading develop broader perspectives, whereas individuals who rarely read may have limited knowledge acquisition. Encouraging the habit of reading, whether through digital or printed books, remains essential in fostering a culture of learning.